Ameliorating cancer cachexia by inhibiting cancer cell release of Hsp70 and Hsp90 with omeprazole. Issue 1 (2nd November 2021) - Liu, Zhelong; Xiong, Jian; Gao, Song; Zhu, Michael X.; Sun, Kai; Li, Min; Zhang, Guohua; Li, Yi‐Ping
Abstract: Background: Cancer cachexia, characterized by muscle and fat tissue wasting, is a major determinant of cancer‐related mortality without established treatment. Recent animal data revealed that cancer cells induce muscle wasting by releasing Hsp70 and Hsp90 as surface proteins on extracellular vesicles (EVs). Here, we test a therapeutic strategy for ameliorating cancer cachexia by inhibiting the release of Hsp70 and Hsp90 using proton pump inhibitor omeprazole. Methods: Omeprazole effect on Hsp70/90 release through EVs by Lewis lung carcinoma (LLC) cells in vitro, serum levels of Hsp70/90 and Hsp70/90‐carrying EVs in LLC tumour‐bearing mice, and LLC‐induced muscle protein degradation pathways in C2C12 myotubes and mice were determined. Omeprazole effect on endolysosomal pH and Rab27b expression in LLC cells were analysed. Results: Omeprazole treatment of LLC cells inhibited Hsp70/90 and Hsp70/90‐carrying EV release in a dose‐dependent manner (1 to 10 μM) and attenuated the catabolic activity of LLC cell‐conditioned medium on C2C12 myotubes. Systemic omeprazole administration to LLC tumour‐bearing mice (5 mg/kg/day subcutaneously) for 2 weeks blocked elevation of serum Hsp70, Hsp90, and Hsp70/90‐carrying EVs, abrogated skeletal muscle catabolism, and prevented loss of muscle function as well as muscle and epididymal fat mass without altering tumour growth. Consequently, median survival increased by 23.3%. Mechanistically, omeprazole increased cancer cell endolysosomal pH level dose‐dependently (0.1 to 1 μM) by inhibiting vacuolar H + ‐ATPase. Further, omeprazole suppressed the highly elevated expression of Rab27b, a key regulator of EV release, in LLC cells. Conclusions: Omeprazole ameliorates cancer cachexia by inhibiting cancer cell release of Hsp70 and Hsp90.